Perpetual motion wind turbine generator for novelty energy harvesting system; conceptual design approach - Alotaibi, Alowaid; Muda, Mohd Khairul Hafiz; Mustapha, Faizal; Abdul Halin, Izhal; Yidris, Noorfaizal (Akademia Baru Publishing, 2022)
This paper deals with optimal design of energy harvesting system with perpetual motion. This design gives flexibility in promoting new sources of generation of electrical energy. The demand of electrical energy is increasing exponentially day by day so it is necessary to find alternative ways of energy generation at low cost. Additionally, by considering the fossil fuels are going to be replenished so the sources should be other than fossil fuels. The substitute of fossil fuels is the renewable energy source. Wind energy is one of major sources of renewable energy. The perpetual motion in this system is another new innovation. The whole system can be used for generating electrical energy without any harm to nature. With this system, the dependency on the continuous natural wind energy source can be eliminated at all. The perpetual motion system will produce the wind to energy harvesting system so that the wind turbine generator can be operated and then generate the electricity. The system also can be run continuously without depending on the current condition of the weather. The energy generated by perpetual motion machines (PMM) are usually discounted by the scientific community since they are considered impossible at industrial level but for small operations PMM can become very efficient.